Дослідження генотипів пшениці м’якої з перенесеним геном GPC-B1 від Triticum turgidum ssp. dicoccoides - Похилько, С.Ю.; Трояновська, А.В.; Степаненко, А.І.; Урбанович, О.Ю.; Дуган, О.М.; Рибалка, О.І.; Моргун, Б.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of our study was to characterize genotypes with gene Gpc-B1 from T. turgidum ssp. dicoccoides in the genome of bread winter wheat pedigrees T. aestivum cv. Kuyalnyk by the finding of recombination between 6B chromosomes of T. aestivum and T. turgidum ssp. dicoccoides, and to detect allelic gene states that cause solid grain. Methods. Polymerase chain reaction was used for molecular genetic analysis. Results. Three generations of wheat hybrid lines were studied for the presence of gene Gpc-B1. The recombination frequency microsatellite loci counted: Хgwm508 – 2.94±1.28%, Xgwm193 – 3.96±1.50%, Xgwm626 – 2.98±1.29% and Xgwm219 – 6.77±2.08%. The polymorphism of gene РinA, РinB was evaluated. Conclusions. The results of DNA marker analysis revealed a promising hybrid line that is a carrier of gene Gpc-B1 from T. turgidum ssp. dicoccoides and contains microsatellite loci of cv. Kuyalnyk. Keywords: Triticum aestivum L., Triticum turgidum ssp. dicoccoides, gene Gpc-B1, PCR, molecular markers.